ANALISIS RISIKO DAN RETURN SAHAM MENGGUNAKAN DOWNSIDE CAPITAL ASSET PRICING MODEL (DCAPM) PADA SAHAM IDX30 - Hazwani Dhiya' Atiq Viatmaja; Hendra Perdana; Evy Sulistianingsih (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2026)
The Indonesian capital market, as an emerging market is characterized by high volatility and an asymmetric return distribution, making the Capital Asset Pricing Model (CAPM) less representative for measuring stock risk and return. This study aims to analyze the relationship between risk and return of IDX30 stocks using the Downside Capital Asset Pricing Model (DCAPM), which focuses on measuring risk from the downside perspective through the estimation of downside beta. The data used consist of daily stock closing prices, the market index, and the risk free rate (BI Rate) from January 2023 to September 2025. A total of 20 stocks that consistently remained in the IDX30 index throughout the observation period were selected as the sample and grouped into portfolios based on their downside beta levels, which were subsequently evaluated using the Omega Ratio. Downside beta was estimated by dividing the asset semicovariance by the market semivariance. The results indicate considerable variation in downside risk among IDX30 stocks. From a financial perspective, a higher downside beta is associated with a higher expected return as compensation for greater downside risk. Moreover, portfolios with higher downside beta can still exhibit relatively good performance, provided that they generate returns exceeding the target return. These findings suggest that the DCAPM and Omega Ratio can serve as effective tools for evaluating stock portfolio risk and performance under asymmetric market conditions.